Integrated garage system with gas detection alert - Mohd Pazli, Ahmad Zayd; Indera Putera, Siti Hazurah; Muhammad Andy Fairoz, Ahmad Iskandar; Othman, Hanunah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
In 2024, over 10,000 vehicles were reported stolen in Malaysia, with the majority being motorcycles, sport utility vehicles (SUVs) and trucks. It is highly desirable to store vehicles in garages to ensure their safety. However, enclosed spaces can pose the threat of exhaust gas poisoning, which includes carbon-monoxide and nitrogen-dioxides, both of which can have adverse health effects. Each year many deaths were reported due to carbon-monoxide poisoning from exhaust gases. Considering these issues, this study proposes an automatic garage with Blynk-automated and Radio Frequency Identification (RFID) enabled security doors, also an Internet-of-Things (IoT) enabled gas detection alert system. The integrated ESP32 microcontroller unit (MCU) which is wi-fi associable is selected as the system’s brain, while a servo motor opens and closes the garage door with an infrared sensor signaling the presence of vehicles. The system is equipped with an MQ135 gas sensor which measures the garage’s air quality and an exhaust fan to expel gases from the garage. Air quality alert is sent to the Telegram application for fast notification. A motion sensor is employed to turn on the light automatically when movement is detected. This mechanism enables the garage to optimize the usage of electricity effectively, thus ensuring an environmentally friendly operation.